Radiographic features of cardiogenic pulmonary oedema in cats with left-sided cardiac disease: 71 cases. Issue 12 (December 2022) - Diana, Alessia; Perfetti, Simone; Valente, Carlotta; Toaldo, Marco Baron; Pey, Pascaline; Cipone, Mario; Poser, Helen; Guglielmini, Carlo
Objectives: The aims of this study were to describe the radiographic features of cardiogenic pulmonary oedema (CPE) in a large group of cats with left-sided cardiac disease, and to determine the association between the radiographic features of CPE and the underlying cardiac disease. Methods: Thoracic radiographs of cats with CPE and echocardiographic evidence of left-sided cardiac disease and left atrial enlargement (LAE) were reviewed, and cardiac silhouette, pulmonary vessels and pulmonary parenchyma evaluation were performed. Interstitial and/or alveolar patterns were classified according to their distribution (ie, diffuse, multifocal or focal) and location (ie, craniodorsal, cranioventral, caudodorsal, caudoventral and perihilar). A Student's t -test and Mann–Whitney U-test, or the two-proportion z-test, were used to compare continuous or categorical variables, respectively, between cats affected by the two most represented cardiac diseases, namely hypertrophic cardiomyopathy (HCM) and restrictive cardiomyopathy (RCM). Results: Seventy-one cats were included; among them, 46 (64.7%) and 13 (18.3%) had presented for HCM and RCM, respectively. Subjective and objective cardiomegaly, and subjective and objective LAE were detected in 97.2% and 91.9% of cats and in 80.3% and 40.6% of cats, respectively. Pulmonary artery abnormalities, in particular caudal pulmonary artery dilation, were found in 77.5% of cats. Pulmonary artery to pulmonary vein ratio = 1 was found in 71.8% and 55% cats on right lateral and ventrodorsal or dorsoventral views, respectively. Interstitial (57.8%) and mixed interstitial–alveolar (38%) pattern, multifocal (84.5%) and symmetrical (75%) distribution with prevalent ventrocaudal (65.6% of cats) and ventrocranial (60.9% of cats) locations were most frequently observed. No difference was found for any of these radiographic features between cats with HCM and RCM. Conclusions and relevance: Moderate-to-severe cardiomegaly and LAE, caudal pulmonary artery and vein dilation, as well as a ventral, multifocal and symmetrical interstitial pulmonary pattern, were the main radiographic features of CPE in evaluated cats. Underlying cardiac disease did not influence the aforementioned radiographic features.